If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + -3 = 2b + -6 Reorder the terms: -3 + 2b = 2b + -6 Reorder the terms: -3 + 2b = -6 + 2b Add '-2b' to each side of the equation. -3 + 2b + -2b = -6 + 2b + -2b Combine like terms: 2b + -2b = 0 -3 + 0 = -6 + 2b + -2b -3 = -6 + 2b + -2b Combine like terms: 2b + -2b = 0 -3 = -6 + 0 -3 = -6 Solving -3 = -6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2a+3(a+4)= | | 8(x+2)-8=17-3x-9+11x | | 60t^4-4at^2+12t= | | (2x-3)(4x-2)= | | 0.33333333333x+10=55 | | x=2x^2+7x+9 | | -a/25=8 | | -4+9(x-2)=16x+3-7x | | .45x+.05(14-x)=.10(-25) | | -8-11=-5x+23 | | 0.80.2=x | | q^2+q-20=0 | | -(6xy-12)+3(5xy+8)= | | (6x+5)-1.3=-1.9 | | 0.33x+10=55 | | 14p^3q^3-21p^2q^2+35pq= | | 400-5x=322-3x | | 2(7)+6+5(7)=55 | | 8789-3434=876x | | -11-r=4(r-4) | | 1/4(3x+5)-1/3(x+7)=6 | | (m)=10 | | 33*.33n=.99n | | 25y^2+10y+1= | | 3x=54+3x | | 14x-28=-56 | | 6(z-4)+8z-3= | | 1/3(x-4)=5x-4(x-1)+22/3 | | 2(x-2)+3=2x+6 | | 2x+7+x=7 | | 22-3x=1 | | 0.5(10x+8)=3x-6 |